Efeitos do tratamento crônico com diferentes doses de Carvedilol sobre a variabilidade de freqüência cardíaca e de pressão arterial de ratos infartados - Dantas, Eduardo Miranda (2012)
The objective was to evaluate the effects of chronic treatment with carvedilol (Carv) on heart rate (HRV) and blood pressure (BPV) variability in rats with myocardial infarction (MI). Methods: Male Wistar rats (body weight 180-250g) were included in the study. The rats underwent MI by ligature of anterior interventricular branch of left coronary artery (N = 40) or a sham operation (SO, N = 29, sham) and randomized to receive vehicle (drinking water) with placebo (Plac, methylcellulose 0.5%) or low (L-Carv, 2 mg/kg/day) or high (H-Carv, 20 mg/kg/day) dose carvedilol: SO-Plac (N=12), SO-L-Carv (N=8), SO-HCarv (N=9), MI-Plac (N=13), MI-L-Carv (N=12) and MI-H-Carv (N=15). Thirty days later, conscious animals underwent hemodynamic evaluation (invasive records of BP and electrocardiogram) for the analysis of BPV and HRV carried out in the time (variance of systolic pressure and R-R interval) and frequency (VLF, LF, HF) domains using the autoregressive modeling with model order set in 16. Ventricular pressure records were obtained by catheterization in the anesthetized animals. Results are shown as mean and standard deviation. Results: MI produced increase in cardiac weight 0.31 ± 0.04 mg/g SO-Plac vs. 0.45 ± 0.10 mg/g MIPlac, P<0.05), impaired left ventricular function with decrease of ventricular systolic pressure (LVSP: 132 ±11 mmHg SO-Plac vs.116 ± 16 mmHg MI-Plac, P<0.05), increase of ventricular initial diastolic (LVDIP: - 4 ± 5 mmHg SO-Plac vs. 9 ± 7 mmHg MI-Plac, P<0.05) and venticular end diastolic (LVDEP: 6 ± 13 mmHg SO-Plac vs. 17 ± 9 mmHg MI-Plac, P<0.05) pressures. We also observed a reduction of LF BPV (61± 22 n.u. SO-Plac vs. 32 ± 25 n.u. MI-Plac, P<0.05) without changes of HRV parameters (variance of R-R: 20.88 ± 12.13 ms2 SO-Plac vs. 29.85 ± 25.20 ms2 MI-Plac, P>0.05). Low dose carvedilol prevented increase in cardiac weight (0.45 ± 0.10 mg/g MI-Plac vs. 0.34 ± 0.04 mg/g MI-LCarv, P<0.05), LVDIP (9 ± 7 mmHg MI-Plac vs. 0 ± 5 mmHg MI-L-Carv, P<0.05) and LVEDP (17 ± 9 mmHg MI-plac vs. 9 ± 6 mmHg MI-L-Carv, P<0.05), but did not change LVSP (116 ± 16 mmHg MI-Plac vs. 114 ± 16 MI-L-Carv mmHg, P>0.05). High dose carvedilol prevented the LVDIP increase (9 ± 7mmHg MI-Plac vs. 1 ± 7 mmHg MI-H-Carv, P<0.05), but did not prevent neither the increase in cardiac weight (0.45 ± 0.10 mg/g MI-Plac vs. 0.42 ± 0.05 mg/g MI-H-Carv, P>0.05) nor of the LVEDP (17 ± 9 mmHg MI-Plac vs. 12 ± 9 mmHg MI-H-Carv, P>0.05) and exacerbated the fall of LVSP (119 ± 10 mmHg MI-Plac vs. 104 ± 12 mmHg MI-H-Carv, P<0.05). None of the treatments affected the BPV (variance of pressure: 13.02 ± 8.30 mmHg2 MI-Plac, 13.69 ± 4.88 mmHg2 MI-L-Carv, 10.91 ± 5.14 mmHg2 MI-H-Carv, P>0.05) nor the HRV (variance of RR: 29.85 ± 25.20 ms2 MI-Plac, 49.64 ± 32.58 ms2 MI-L-Carv, 30.90 ± 33.00 ms2 MIH-Carv, P>0.05). Conclusion: Low dose carvedilol improved hemodynamic parameters and prevented the development of cardiac hypertrophy after MI. These effects seem to be independent of adjustments in the autonomic balance to the heart and vessels, since they did not have a significant impact on the spectral components of HRV and VPA.